2020
DOI: 10.1002/jha2.1
|View full text |Cite
|
Sign up to set email alerts
|

Partial omission of bleomycin for early‐stage Hodgkin lymphoma patients treated with combined modality therapy: Does incomplete ABVD lead to inferior outcomes?

Abstract: Classical Hodgkin lymphoma (HL) patients achieve excellent outcomes; therefore, treatment de‐escalation strategies to spare toxicity have been prioritized. In a large randomized trial of early‐stage HL patients, omission of chemotherapeutic agents including bleomycin from the standard ABVD (doxorubicin, bleomycin, vinblastine, dacarbazine) regimen was not found to be noninferior; however, the effect of partial omission is unknown. We investigated the effect of bleomycin omission on outcome for 150 early‐stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…A positive interim PET can direct early treatment intensification to improve prognosis ( Eichenauer et al, 2018 , Ansell, 2020 ). A negative interim PET can lead to de-escalation strategies to minimize treatment-related toxicity with no negative impact on outcome ( Ansell, 2020 , Gunther et al, 2020 ). In our case, interim PET-CT was replaced by WB-DWI/MRI.…”
Section: Discussionmentioning
confidence: 99%
“…A positive interim PET can direct early treatment intensification to improve prognosis ( Eichenauer et al, 2018 , Ansell, 2020 ). A negative interim PET can lead to de-escalation strategies to minimize treatment-related toxicity with no negative impact on outcome ( Ansell, 2020 , Gunther et al, 2020 ). In our case, interim PET-CT was replaced by WB-DWI/MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Gunther et al demonstrated that partial omission of bleomycin resulted in a 99% freedom from relapse at 8 years. 21…”
Section: Elderly Hodgkin Lymphomamentioning
confidence: 99%
“…Finally, a diagnosis of classical Hodgkin lymphoma – mixed cellularity (Lugano II) was established. The patient received 4 cycles of AVD (adriamycin, vinblastine, dacarbazine; bleomycin was omitted due to patient age) chemotherapy 5 and attained complete metabolic remission confirmed by PET-FDG. DA was continued during treatment at a reduced dose of 50 mg except on chemotherapy days.…”
Section: Case Reportmentioning
confidence: 99%